1997
DOI: 10.2754/avb199766030141
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Changes in Electrolyte Concentration in Plasma and Erythrocytes in Two-week-old Calves

Abstract: Skotnicka E., W. F. Skrzypczak, M. Ozgo: Circadian Changes in Electrolyte Concentrations in Plasma and Erythrocytes of Two-week-old Calves. Acta vet. Brno 1997, 66: 141-146.The aim of this study was to determine changes in the content of Na, K, CI, Ca, Mg and P in the plasma and erythrocytes of 14-day-old calves with simultaneously performed evaluation of the occurrence and analysis of the rhythms.The studies were carried out on a group of 10 Black and White, clinically healthy female calves aged 14 days. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Muszczynski [35] and Skotnicka [48], in goats, and Skotnicka et al [44], in calves, did not observe diurnal changes in plasma osmolality. However Skotnicka [48], in a study on pregnant goats, observed significant plasma osmolality differences between maximum (in the evening) and minimum (in the morning).…”
Section: Blood Plasma Electrolytesmentioning
confidence: 97%
“…Muszczynski [35] and Skotnicka [48], in goats, and Skotnicka et al [44], in calves, did not observe diurnal changes in plasma osmolality. However Skotnicka [48], in a study on pregnant goats, observed significant plasma osmolality differences between maximum (in the evening) and minimum (in the morning).…”
Section: Blood Plasma Electrolytesmentioning
confidence: 97%
“…Skotnicka et al (1997) in calves, did not observed diurnally changes of plasma osmolality. However, Kanervo et al (1991) and Windle et al (1992) observed circadian changes of plasma osmolality in rats, with the highest values around midnight, in the middle of animals' activity period.…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, plasma Cl -concentration in nonpregnant and pregnant goats remained relatively stable. Similarly Muszczyƒski et al (1996) in pregnant goats and Skotnicka et al (1997) in calves did not find any diurnal variations in Cl -plasma concentrations.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations